(untitled) (Zoological Records and Reviews, 2024)
Selecting among available conservation strategies for endangered animal species requires rigorous evaluation of intervention effectiveness, cost-efficiency, and long-term viability under projected future conditions. This study evaluates the outcomes of six conservation strategies – in situ habitat protection, habitat restoration, ex situ captive breeding with reintroduction, legal protection enforcement, community-based conservation, and species-specific research programmes – applied to sixteen Critically Endangered (CR) or Endangered (EN) vertebrate species across Austria, Germany, and Italy between 2005 and 2023. Strategy outcomes were quantified using population trend indices derived from long-term monitoring data (n = 18,284 individual records), population viability analysis (PVA) projections, and cost-effectiveness ratios (species-years of population stability per 10,000 EUR invested). In situ habitat protection combined with habitat restoration achieved the highest mean population trend improvement (+2.8% per year; 95% CI: +1.9 to +3.7%) and the highest cost-effectiveness ratio (4.8 species-years / EUR 10,000) across the sixteen species. Ex situ captive breeding with reintroduction achieved the highest single-species absolute recovery (European bison Bison bonasus: population increase +284 individuals over 18 years) but the lowest cost-effectiveness ratio (0.8 species-years / EUR 10,000). Community-based conservation was the most cost-effective strategy for species in human-dominated landscapes (mean ratio 3.6 species-years / EUR 10,000). PVA projections under current strategy conditions show that eleven of sixteen species have > 90% probability of persistence over 100 years, while five remain at high extinction risk requiring strategy intensification. These findings provide an evidence-based framework for strategy selection and resource allocation in national species recovery plans under EU Habitats Directive reporting obligations.